Epidemiological profile of reported cases of suicide attempts by exogenous intoxication in the state of Piauí (Research, Society and Development, 2020)
The present study aims to describe the epidemiological profile of reported cases of suicide attempts by exogenous intoxication in the state of Piauí in the last 5 years (2015-2020). This is a quantitative and descriptive cross-sectional design. The data were extracted from the DATASUS platform, including the following variables: sex, age group, race, toxic agent and notification municipality. The data were organized and analyzed using descriptive statistics. 3,400 cases of suicide attempts with the use of toxic agents were detected in the state of Piauí; and, through this total, it was found that 76.18% were female, 53.35% were in the young adult range, 54.15% had brown skin, 77.74% used drugs in the self-inflicted injury and 53, 59% were notifications from the city of Teresina. The identification of the epidemiological profile of the studied population indicated essential aspects for improving public health approaches. Thus, it was found that, for the cases evaluated, the prevalence was female, aged between 20-39 years, brown, who used drugs as toxic agents and residing in the state capital.